2007
DOI: 10.1001/archotol.133.8.796
|View full text |Cite
|
Sign up to set email alerts
|

Regional Recurrence of Squamous Cell Carcinoma of the Nasal Cavity

Abstract: To demonstrate whether the regional recurrence (RR) of squamous cell carcinoma (SCC) of the nasal cavity is higher than previously suspected. Data Sources: Original articles, including a previously published series from our institution, were identified from systematic searches of the MEDLINE database. Study Selection: Studies that analyzed tumors other than SCC or tumors from sites other than the nasal cavity were excluded. Studies that did not report an RR were also excluded. Data Extraction: Studies identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…Five-year disease specific survival (DSS) ranges from 50 to 80% [611]. Nodal involvement, advanced tumor stage and larger tumor size are worse prognostic factors for outcome [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five-year disease specific survival (DSS) ranges from 50 to 80% [611]. Nodal involvement, advanced tumor stage and larger tumor size are worse prognostic factors for outcome [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Nodal involvement, advanced tumor stage and larger tumor size are worse prognostic factors for outcome [1, 2]. Nodal involvement represents a strong worse prognostic factor that results in almost a halving of survival [611]. A recently published meta-analysis among 1283 patients with sinonasal carcinomas revealed that elective neck treatment could reduce the risk of regional recurrence [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scurry et al [53] publizierten eine Metaanalyse und wiesen auf eine hohe Rezidivrate bei dieser Tumorentität hin. McCollough et al [7] fanden in 25 % der T4-Tumoren (AJCC) regionale Lymphknotenmetastasen und sprechen sich daher für eine elektive regionale Bestrahlung in dieser Subgruppe aus.…”
Section: Elektive Therapie Der Regionalen Lymphknotenunclassified